Equivalence between Increasing Returns and Comparative Advantage as the Determinants of Intra-industry Trade: An Industry Analysis for Korea - Honggue Lee (East Asian Economic Review (EAER), 2018)
A two-part model is estimated to see if increasing returns and comparative advantage are empirically equivalent in explaining intra-industry trade. The model has separate mechanisms for determining the occurrence and the extent of intra-industry trade. Estimation is based on an augmented Grubel-Lloyd index derived from the data set on SITC 7 goods at the 3-digit SITC (Revision 4) for country pairs in which Korea is fixed as a source country. Estimation results show that both increasing returns and comparative advantage can explain the occurrence and the extent of intra-industry trade.
Keywords: F11; F12; F14; 330; Grubel-Lloyd Index; Increasing Returns; Comparative Advantage; Intra-industry Trade; Trade Costs; Export Margins; Two-part Model